Implementation of Tafsîr Ûlul Albâb in Indonesian Islamic Education - Nurhadi, Rofiq; Sert, Hüseyin Emin; Wahyudi, Jarot (Indonesian Academy of Social and Religious Research (IASRR), 2024)
Islam views the holy book as not only regulating matters of worship which are vertical between servants and God. The holy book is also seen as a guide for humans in managing all world affairs, including the world of education. The development of Islamic education today, directly or indirectly, often links its vision to the formation of the ûlul albâb generation (QS. Ali Imran; 190-194). Even though the vision is the same, the implementation of Islamic education often appears to vary. Islamic educational institutions in Indonesia exist in the form of pesantren, boarding schools, madrasah, and also schools. So what is meant by the ûlul albâb generation and how is Islamic education implemented in producing the ûlul albâb generation? This research is intended to find out the views of commentators regarding the meaning of ûlul albâb and at the same time to describe the models of Islamic education that have developed to date in Indonesia. This research is library research and the methods used are the maudlu'i (thematic) interpretation method and the qualitative descriptive method. Based on this research, it can be concluded that ûlul albâb is a self-image that combines academic qualities, spirituality, and charity. In this perspective, Islamic education is a process of improving the quality of humanity in its various dimensions, namely making scholars who believe and do good deeds. To achieve this goal, Islamic education in Indonesia is developing an integrative education model, namely institutional integration and curriculum integration.